1989
DOI: 10.1139/x89-224
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of photosynthetic activity of nursery-grown Piceaglauca seedlings using an integrating fluorometer to monitor variable chlorophyll fluorescence

Abstract: Photosynthetic activity of intact nursery-grown white spruce (Piceaglauca (Moench) Voss) seedlings was assessed by measuring CO2 exchange (apparent photosynthesis) and normalized, integrated variable chlorophyll fluorescence emission. Agreement between fluorescence and apparent photosynthesis indicated that photosynthetic inactivation of seedlings from selected seedlots began in mid-August and approached completion in late October. Inactivation occurred somewhat earlier in northern seedlot seedlings than in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 0 publications
0
10
0
2
Order By: Relevance
“…A decline in F v /F m is a good indicator of photoinhibitory damage caused by light when plants are subjected to a wide range of environmental stresses, including chilling (Baker et al 1983), freezing (Strand and Öquist 1985) and drought (Ögren and Öquist 1985;Mena-Petite et al 2000), so that the stress caused by storage also alters this ratio (Fig. If after transplanting the fluorescence parameters do not recovery it could be considered an indication of reduced seedling vigour (Vidaver et al 1989) and it could put in risk the post-planting survival (Fig. Thus, the increase of the needle electrolyte leakage, indicative of disruption of membranes, will be responsible for the decrease in the photochemical efficiency (Fig.…”
Section: Gas Exchange Parametersmentioning
confidence: 99%
“…A decline in F v /F m is a good indicator of photoinhibitory damage caused by light when plants are subjected to a wide range of environmental stresses, including chilling (Baker et al 1983), freezing (Strand and Öquist 1985) and drought (Ögren and Öquist 1985;Mena-Petite et al 2000), so that the stress caused by storage also alters this ratio (Fig. If after transplanting the fluorescence parameters do not recovery it could be considered an indication of reduced seedling vigour (Vidaver et al 1989) and it could put in risk the post-planting survival (Fig. Thus, the increase of the needle electrolyte leakage, indicative of disruption of membranes, will be responsible for the decrease in the photochemical efficiency (Fig.…”
Section: Gas Exchange Parametersmentioning
confidence: 99%
“…Chlorophyll fluorescence has been increasingly used to understand both the mechanism of photosynthesis and the factors affecting it. Vidaver et al (1989) suggested that chlorophyll fluorescence can rapidly provide useful information about photosynthetic responses to environmental stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorophyll fluorescence has been increasingly used to understand both the mechanism of photosynthesis and the factors affecting it. Vidaver et al (1989) suggested that chlorophyll fluorescence can rapidly provide useful information about photosynthetic responses to environmental stresses.The objective of this study was to evaluate the effects of three different shade levels and unshaded conditions on the survival, morphology, and chlorophyll fluorescence of N. alessandrii seedlings cultivated in containers. The study assessed the hypothesis that N. alessandrii seedlings require some degree of protection from direct sunlight in their early stages of development.…”
mentioning
confidence: 99%
“…Autumn frosts may significantly decrease leaf or needle area, thus negatively affecting the seedling's photosynthetic capacity and its ability to initiate new roots. During hardening, the photosynthetic apparatus of coniferous species gradually adapts to decreasing temperatures (Öquist and Huner 2003;Vidaver et al 1989). A decrease in photosynthesis or the mass of photosynthetically active foliage as a result of early frost may reduce root initiation and growth, therefore compromising root plug cohesion.…”
Section: Introductionmentioning
confidence: 99%